A Systematic Community-Based Participatory Approach to Refining an Evidence-Based Community-Level Intervention: The HOLA Intervention for Latino Men Who Have Sex With Men. Issue 4 (July 2013) - Rhodes, Scott D.; Daniel, Jason; Alonzo, Jorge; Duck, Stacy; García, Manuel; Downs, Mario; Hergenrather, Kenneth C.; Alegría-Ortega, José; Miller, Cindy; Boeving Allen, Alex; Gilbert, Paul A.; Marsiglia, Flavio F.
Our community-based participatory research partnership engaged in a multistep process to refine a culturally congruent intervention that builds on existing community strengths to promote sexual health among immigrant Latino men who have sex with men (MSM). The steps were the following: (1) increase Latino MSM participation in the existing partnership, (2) establish an Intervention Team, (3) review the existing sexual health literature, (4) explore needs and priorities of Latino MSM, (5) narrow priorities based on what is important and changeable, (6) blend health behavior theory with Latino MSM's lived experiences, (7) design an intervention conceptual model, (8) develop training modules and (9) resource materials, and (10) pretest and (11) revise the intervention. The developed intervention contains four modules to train Latino MSM to serve as lay health advisors known as Navegantes . These modules synthesize locally collected data with other local and national data; blend health behavior theory, the lived experiences, and cultural values of immigrant Latino MSM; and harness the informal social support Latino MSM provide one another. This community-level intervention is designed to meet the expressed sexual health priorities of Latino MSM. It frames disease prevention within sexual health promotion.